P2.122 HIV is an Independent Predictor of Aortic Pulse Wave Velocity. (13th July 2013) - Wainwright, E C; Rider, O J; Asaad, M; Ntusi, N; Hancock, G; Pitcher, A; Clarke, K; Dorrell, L; Neubauer, S; Holloway, C
Abstract : Background: Patients with HIV infection are at increased risk of cardiovascular events. Many potential causes have been proposed, including immunodeficiency, chronic immune activation and traditional cardiovascular risk factors. However, metabolic and anthropometric abnormalities associated with HIV and antiretroviral therapy are likely to play an important role in cardiovascular disease development. These metabolic abnormalities are similar to the metabolic syndrome (MS), an established risk factor for cardiovascular mortality. This study aimed to investigate the relationship between HIV infection and a surrogate measure of cardiovascular risk and compare this to the risk associated with metabolic syndrome. Methods: 90 patients with HIV and 113 without HIV underwent magnetic resonance imaging to determine aortic pulse wave velocity (PWV), a clinical measure of aortic stiffness, predictive of cardiovascular mortality. Subjects were divided into 4 groups: (1) HIV-ve/MS-ve, (2) HIV-ve/MS+ve, (3) HIV+ve/MS-ve and (4)HIV+ve/MS+ve. Results: Aortic PWV was 16% higher in the HIV+ve/MS-ve group when compared to HIV-ve/MS-ve (6.2 ± 1.9 vs 5.4 ± 1.0m/s, p = 0.008) and similar to that observed in the HIV-ve/MS+ve group (6.2 ± 1.9 vs 6.3 ± 1.7 m/s, p > 0.99). The HIV+ve/MS+ve group had 38% higher PWV than HIV-ve/MS-ve group (p < 0.001) and 19% higher PWV than HIV+ve/MS-ve subjects (p = 0.049). On multivariable regression age (b = 0.07, p < 0.001), systolic blood pressure (b = 0.02, p = 0.02) and treated HIV infection (b = 0.62, p = 0.01) were all independent predictors of aortic PWV (overall R2 = 0.34, p < 0.001). Conclusion: Treated HIV infection is associated with increased aortic stiffness. The magnitude of this effect of treated HIV is similar to that observed with the metabolic syndrome. Furthermore HIV and MS are additive in their detrimental effects on vascular function.